Iron Biochemistry is Correlated with Amyloid Plaque Morphology in an Established Mouse Model of Alzheimer's Disease. Issue 10 (19th October 2017) - Telling, Neil D.; Everett, James; Collingwood, Joanna F.; Dobson, Jon; van der Laan, Gerrit; Gallagher, Joseph J.; Wang, Jian; Hitchcock, Adam P.
Summary: A signature characteristic of Alzheimer's disease (AD) is aggregation of amyloid-beta (Aβ) fibrils in the brain. Nevertheless, the links between Aβ and AD pathology remain incompletely understood. It has been proposed that neurotoxicity arising from aggregation of the Aβ1-42 peptide can in part be explained by metal ion binding interactions. Using advanced X-ray microscopy techniques at sub-micron resolution, we investigated relationships between iron biochemistry and AD pathology in intact cortex from an established mouse model over-producing Aβ. We found a direct correlation of amyloid plaque morphology with iron, and evidence for the formation of an iron-amyloid complex. We also show that iron biomineral deposits in the cortical tissue contain the mineral magnetite, and provide evidence that Aβ-induced chemical reduction of iron could occur in vivo . Our observations point to the specific role of iron in amyloid deposition and AD pathology, and may impact development of iron-modifying therapeutics for AD. Graphical Abstract: Highlights: Chemically reduced pure ferrous iron is directly associated with amyloid pathology Diffuse amyloid deposits could comprise an iron-amyloid complex Magnetic signature of particulate magnetite detected with varying oxidation state Abstract : Telling et al. demonstrate an enhanced role for iron in Alzheimer's disease pathology, having implications for neurodegeneration, early-stage diagnosis by MRI, and possible treatments based on metal chelation.